Management practices and competencies of senior managers for effective management in the State of Chile - Castro, Carlos (Journal Studies of Public Policy, 2016)
This paper has a primarily exploratory feature, which contemplates the use of quantitative and qualitative methods and analysis techniques, with the purpose to develop new and significant contributions to the study of management for the Senior Public Servers of Chile (SADP), considering its cultural and institutional reality. The main instrument for the collection of primary data is an electronic survey to all public managers of first and second hierarchical level selected by the SADP, after an extensive validation process. Subsequently, through a focus group with managers of first hierarchical level, seeks to validate and contrast results, concluding with implications for public policy towards improving the system and enhancement of new lines of research in the area of public management. The relevance of this research is based on the importance and impact of the quality of public management at the organizational level in the State. In the same vein, the literature shows the importance of leadership and quality of managers as well as the central role of the professionalization of public management reform process in any country.